Acquired Melanonychia in Chilean Patients with Essential Thrombocythemia Treated with Hydroxyurea: A Report of 7 Clinical Cases and Review of the Literature. (7th February 2013) - Murray, Nigel P.; Tapia, Pablo; Porcell, Jose; Echavarria, Maximiliano; Suazo, Hernán
Abstract : Longitudinal melanonychia has been associated with a range of drugs, especially chemotherapeutic agents. We report 7 cases of melanonychia associated with the use of hydroxycarbamide for essential thrombocythemia. Of a patient population of 27, 7 (26%) developed melanonychia over a period of 2–7 years, and was not dose dependent. The high incidence of melanonychia in Chilean patients may be in part due to their Hispanic descent or to the high levels of UV radiation found in Santiago.